Dietary spinach reshapes the gut microbiome in an Apc-mutant genetic background: mechanistic insights from integrated multi-omics. (1st January 2021) - Chen, Ying-Shiuan; Li, Jia; Menon, Rani; Jayaraman, Arul; Lee, Kyongbum; Huang, Yun; Dashwood, Wan Mohaiza; Zhang, Ke; Sun, Deqiang; Dashwood, Roderick H.
ABSTRACT: Complex interrelationships govern the dynamic interactions between gut microbes, the host, and exogenous drivers of disease outcome. A multi-omics approach to cancer prevention by spinach (SPI) was pursued for the first time in the polyposis in rat colon (Pirc) model. SPI fed for 26 weeks (10% w/w, freeze-dried in the diet) exhibited significant antitumor efficacy and, in the Apc-mutant genetic background, β-catenin remained highly overexpressed in adenomatous polyps. However, in both wild type and Apc-mutant rats, increased gut microbiome diversity after SPI consumption coincided with reversal of taxonomic composition. Metagenomic prediction implicated linoleate and butanoate metabolism, tricarboxylic acid cycle, and pathways in cancer, which was supported by transcriptomic and metabolomic analyses. Thus, tumor suppression by SPI involved marked reshaping of the gut microbiome along with changes in host RNA-miRNA networks. When colon polyps were compared with matched normal-looking tissues via metabolomics, anticancer outcomes were linked to SPI-derived linoleate bioactives with known anti-inflammatory/ proapoptotic mechanisms, as well as N -aceto-2-hydroxybutanoate, consistent with altered butanoate metabolism stemming from increased α-diversity of the gut microbiome. In colon tumors from SPI-fed rats, L-glutamate and N -acetylneuraminate also were reduced, implicating altered mitochondrial energetics and cell surface glycans involved in oncogenic signaling networks and immune evasion. In conclusion, a multi-omics approach to cancer prevention by SPI provided mechanistic support for linoleate and butanoate metabolism, as well as tumor-associated changes in L-glutamate and N -acetylneuraminate. Additional factors, such as the fiber content, also warrant further investigation with a view to delaying colectomy and drug intervention in at-risk patients.